Spina Bifida Sacralis Occulta from Ancient Greek Sicily (Pozzanghera Necropolis, Leontinoi, 6th–4th Century BC): Anatomical, Anthropological and Ethnomedical Considerations on the Insular Presentation of this Congenital Anomaly - Melintenda, Sebastiano; Varotto, Elena; Pappalardo, Eleonora; Guzzardi, Lorenzo; Papa, Veronica; Palermo, Dario; Galassi, Francesco M. (Anthropological Review, 2023)
In this article a case of spina bifida sacralis occulta (SBSO) from the Pozzanghera necropolis of the ancient Greek colony of Leontinoi (Sicily) and archaeologically dated to the 6th–4th century BC is morphologically analysed and discussed. An ethnomedical excursus on the knowledge and impact of this condition in Sicilian history is offered. Although SBO is one of the most frequent congenital anomalies in the global palaeopathological record, a comprehensive literature search did not yield results for the history of Sicily before Christ, hence this case enriches existing knowledge on the historical presentation of this vertebral congenital anomaly in this region.